A populizmus elemei a Jobbik politikájában - Hirth Zsófia (Móra Akadémia, 2018)
The essay reflects to the Jobbik Magyarországért Mozgalom, on 2013, when the extremly right side part turned to be catch all part and also research what could be the sequels. The essay studies why did change the part his way. Which were those politics processions, causes and societal effects what make the part to change the tactics. Why happened, that Vona Gábor, the president of Jobbik took a pohoto of him with puppies and the extremly, racist, anti-semite rhetoric get reductioned and more radical theories removed from the agenda. New theories appeared on the agenda, what can catch wider voters, as the Jobbik thinks. My hypothesis is the conception is the populism, what means rhetoricalcommunicational turning. Int he essay I carefully introduce the populism and after I present how does it works in practice.